Recent Progresses on Applications of Conducting Polymers for Modifying Electrode of Rechargeable Batteries - Huanrong Zhang (Wiley-VCH, 2021)
In recent years, the rapid development of electric vehicles, smart grids, and portable electronic devices have given a boost to energy storage devices represented by rechargeable batteries. Seeking for reliable security, cost‐effectiveness, and especially high energy density of rechargeable batteries is the crucial demand. The key to improve energy density of rechargeable batteries is adopting high theoretical capacity electrodes or reducing the content of nonredox components. Unfortunately, some problems such as poor cycle stability and low rate performance caused by poor conductivity and unstable structure limit the application of high‐capacity electrodes. Conducting polymers (CPs) are widely used to modify electrode materials to promote the carrier transport and suppress the volume expansion during cycles due to their good conductivity, electroactivity, and machinability. In this Review, the conductive mechanisms, synthesis methods, and the applications in modifying electrodes with CPs are discussed. Also, the recent progresses about CPs‐modified electrodes including coating, intercalation, and carbonization in rechargeable batteries are summarized. Finally, the challenges and the further developments for modifying electrodes with CPs, which aims to provide the assistance for developing high‐performance CPs composite electrodes, are proposed.